Dual modality feeders: a group of human milk feeders with unique practices and needs - Ksenia Kholina; Jennifer Brady; Erna Snelgrove-Clarke; Melissa D Rossiter; Kyly C Whitfield (Cambridge University Press, 2023)
Abstract Objective: Dual modality feeding (DMF) - feeding human milk interchangeably from the breast and from a bottle - comes with unique practical, emotional and relational challenges, as well as support needs. Yet, there is little research that explores the experiences of individuals who use DMF in the Canadian context. The aim of this study is to explore the practices, challenges, reasons and enablers of DMF. Design: Repeat, semi-structured one-on-one interviews were conducted at 8 weeks and 22 weeks postpartum. Interview transcripts were thematically analysed using a critical feminist lens. Setting: Nova Scotia, Canada. Participants: Ten DMF mothers. Results: DMF practices were influenced by a mix of social and material circumstances, including breast-feeding challenges, the involvement of support persons, finances and access to lactation support. Individuals who predominantly fed at the breast expressed milk strategically to mitigate transitory breast-feeding challenges, for convenience under specific circumstances, and to share feeding responsibilities with other caregivers for personal and practical reasons. Individuals who mainly bottle-fed did so due to long-term breast-feeding challenges or a need to return to employment. Enablers of successful DMF were consistent between the two groups and included practical, personal and relational aspects. Conclusions: DMF is a unique practice compared to feeding human milk solely from the breast or bottle. Despite the potential growing prevalence of DMF, it is currently understudied and inadequately addressed in existing support programmes in Nova Scotia. Tailored programming and public messaging are needed to support DMF families.